2004
DOI: 10.1038/sj.ejcn.1601792
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and vitamin A intake and status in a national sample of British young people aged 4–18 y

Abstract: Objective: To examine zinc and vitamin A intake and status and associated dietary, socio-demographic, lifestyle and physiological factors in British young people. Design: National Diet and Nutrition Survey of young people aged 4-18 y. Setting: Great Britain, 1997. Subjects: Complete 7-day weighed dietary records were provided by 1520 participants, while 1193 provided blood samples. Results: A total of 13 and 11% of participants respectively reported low dietary intakes of zinc and vitamin A (retinol equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
22
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
7
22
2
1
Order By: Relevance
“…Cereals, together with meat and dairy products, were the major contributors of dietary Zn, which is in agreement with previous studies conducted among Mediterranean adult populations in southern Spain (19) . Moreover, similar data have been reported in other epidemiological studies with adolescents in the UK (20) and Germany (21) , with children in New Zealand (22) and in the total Italian diet (23) . Fish and seafood, despite being important sources of Zn, made minor contributions to daily Zn intakes because these foods were partially rejected by some of the participants, which may account for their relatively low consumption (0?4 servings/d).…”
Section: Zn Intakesupporting
confidence: 88%
“…Cereals, together with meat and dairy products, were the major contributors of dietary Zn, which is in agreement with previous studies conducted among Mediterranean adult populations in southern Spain (19) . Moreover, similar data have been reported in other epidemiological studies with adolescents in the UK (20) and Germany (21) , with children in New Zealand (22) and in the total Italian diet (23) . Fish and seafood, despite being important sources of Zn, made minor contributions to daily Zn intakes because these foods were partially rejected by some of the participants, which may account for their relatively low consumption (0?4 servings/d).…”
Section: Zn Intakesupporting
confidence: 88%
“…Plasma Zn is not reported in the NDNS of adults but according to an analysis of the NDNS of children and adolescents, despite Zn intakes being below the RNI, Zn intakes and status appear to be generally adequate in young people aged 4-18 years (76) . The analysis shows that plasma Zn concentrations are 'low' in only 2 .…”
Section: Zincmentioning
confidence: 93%
“…(b) The authors are incorrect in stating that tyrosine cannot be synthesized in brain from phenylalanine. (c) Despite the authors' statement, even very large increases in phenylalanine levels produced by aspartame administration to rats do not suppress catecholamine synthesis rate (Fernstrom et al, 1991) Dietary zinc intake in the investigation of 'zinc and vitamin A intake and status in a national sample of British young people aged 4-18 years' (Thane et al, 2004) was reported to be 'adequate' for most of the population. This conclusion was based on:…”
mentioning
confidence: 99%
“…For example, 88 samples (8%) were collected from young people who had consented to the fasting procedure but had eaten or drunk something in the morning before blood sample was obtained (Gregory et al, 2000). (e) In this National Diet and Nutrition Survey, poor zinc status was defined as a concentration below 10.71 mmol l À1 for a fasting sample (Gregory et al, 2000;Thane et al, 2004). This cutoff point of zinc status was based on the data of the second National Health and Nutrition Examination Survey (Pilch and Senti, 1985) and the 10.71 mmol l À1 is a value derived from two standard deviations below the mean plasma zinc concentration for US adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation